Peran Religiusitas Sebagai Moderasi Determinan Tindakan Penggelapan Pajak - Dwi Pujiastuti; Fany Indriyani (JAS (Jurnal Akuntansi Syariah), 2021)
The purpose of this research is to show the effect of fairness of tax collection, subjective norms, taxation system, and tax sanctions on tax evasion, which is moderated by religiosity. This study uses a quantitative approach. The data used are primary data derived from questionnaires. The population used are entrepreneurs registered with the cooperative service, small and medium enterprises in the city of Salatiga. The sampling technique used purposive sampling to obtain as many as 33 samples. Data analysis using multiple linear regression and moderated regression analysis (MRA). The results showed that the fairness of tax collection, taxation system, and tax sanctions could not affect the act of tax evasion. Then religiosity cannot be a moderator in the act of tax evasion. However, subjective norms have been shown to influence tax evasion. Subjective norms are suggestions or invitations to those closest to them to comply with tax regulations not to commit tax evasion. Religiosity cannot reduce tax evasion because it is influenced by external factors so that religiosity as an individual value embedded in the person cannot be a component that reduces tax evasion.